Fc-modification of anti-PcrV gene-encoded antibodies modulates complement-mediated killing of Pseudomonas aeruginosa - Eisenhauer, Jillian; Dublin, Spencer; Choi, Jihae; Trachtman, Abigail R.; Chu, Jacqueline D.; Custodio-Zegarra, David; Bharti, Suman; Bhardwaj, Bhavya; Bai, Shuangyi; Witt, William T.; Gutierrez, Maria de la Paz; Miller, Sarah J.; et al. (Frontiers in Immunology, 2025)
Pseudomonas aeruginosa is a high priority multi-drug-resistant (MDR) bacterial pathogen with increasing resistance against broad-spectrum antibiotics. Multiple efforts are ongoing to develop anti-pseudomonal vaccines however achieving meaningful outcomes has been challenging in human clinical trials. Monoclonal antibodies (MAbs) are emerging as promising biologics for targeting P. aeruginosa infections and engineering strategies that bridge engagement with innate immune mechanisms like complement-mediated antibody dependent phagocytosis may be beneficial to improve bacterial clearance. We previously described both protection and long-term expression of synthetic DNA-encoded MAb (DMAb) expressing the anti-PcrV MAb V2L2-MD. Here, we show that modification of DMAb-V2L2-MD with an Fc-point mutation designed to enhance complement engagement demonstrates improved binding to C1q, C3 deposition, and improved opsonophagocytic killing. This Fc-modified DMAb reduced P. aeruginosa bacteria burden in lungs and nasal washes in a lethal acute murine intranasal infection model. These data highlight the importance of tailoring downstream antibody innate effector functions to improve clearance of difficult-to-treat bacteria like MDR P. aeruginosa.